Energy conversion modes depending on the outdoor temperature for an air handling unit with a heat pump - Frik, Anton; Martinaitis, Vytautas; Bielskus, Juozas (International Conference “Environmental Engineering”, 2020)
Modern air handling units (AHU) are increasingly finding solutions in which the main energy transformers are an air heat pump (HP) and a heat recovery exchanger (HRE). The energy conversion modes of such devices are constantly changing in accordance with the constant change on the state of the outdoor air (temperature, humidity). Flexibility, being able to respond to ever-changing ambient air parameters, is an important feature of energy transformation component mode control. The overall seasonal efficiency of the air handling unit depends on this. In this work, a thermodynamic analysis of the characteristic energy transformations of the air handling unit is performed, linking the outdoor and ventilated indoor air and HP refrigerant states, flow rates and component loads. Such parametric analysis with respect to the changing outdoor air temperature allowed to clearly reveal, through various indicators, the influence of the individual components on the operating efficiency of the air handling unit. Combinations of parameters have been obtained that enable the selection of the optimal control concept for the energy conversion mode of the components in the air handling unit (component loads, fluids state parameters and flow rates) over a wide range of outdoor air temperatures.